Case reportsPartial resection of giant rhabdomyoma of the right ventricle in a neonate - Bezuška, Laurynas; Lebetkevičius, Virgilijus; Lankutis, Kęstutis; Tarutis, Virgilijus (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Tumors are rare in neonates. The most common type is a benign rhabdomyoma. Rhabdomyoma is self-regressing with time. However, if a tumor is huge and causing hemodynamic instability, surgery is indicated. We present successful cardiac surgery for partial removal of a giant rhabdomyoma tumor in the right ventricle of a 7-day-old neonate and spontaneous regression of the remnant tumor mass at follow-up.